Pan-African Banks : Opportunities and Challenges for Cross-Border Oversight - Enoch, Charles (Departmental Papers; Departmental Paper ;, 2015)
Pan-African banks are expanding rapidly across the continent, creating cross-border networks, and having a systemic presence in the banking sectors of many Sub-Saharan African countries. These banking groups are fostering financial development and economic integration, stimulating competition and efficiency, introducing product innovation and modern management and information systems, and bringing higher skills and expertise to host countries. At the same time, the rise of pan-African banks presents new challenges for regulators and supervisors. As networks expand, new channels for transmission of macro-financial risks and spillovers across home and host countries may emerge. To ensure that the gains from cross border banking are sustained and avoid raising financial stability risks, enhanced cross-border cooperation on regulatory and supervisory oversight is needed, in particular to support effective supervision on a consolidated basis. This paper takes stock of the development of pan-African banking groups; identifies regulatory, supervisory and resolution gaps; and suggests how the IMF can help the authorities address the related challenges.